A High Variability of Mixed Infections and Recent Recombinations of Hepatitis B Virus in Laos - Andernach, Iris E. (Public Library of Science, 2012)
In Lao PDR, where more than 8% of the population are chronic carriers of HBsAg, multiple genotypes and subgenotypes co-circulate and are prone to generate recombinant viruses. Phylogenetic analyses of multiple clones per donor revealed mixed infections of subgenotypes B1, B2, B4, C1, C5, I1 and I2 in almost 6% of HBsAg positive rejected blood donors. Recombination analyses and distance calculations furthermore showed that about 65% (17/26) of the mixed infected donors showed recombinations in the S-gene alone, involving the predominant genotypes B and C. These results suggest that, at least in Laos, hepatitis B virus (HBV) mixed infections lead to frequent recombinations. In many donors with recombinant strains, the recombinant fragment and a non-recombinant strain of the same genotype co-existed (127/185 analysed recombinant fragments). For a large proportion of these (60/127), the most closely related known virus was found, although not always exclusively, in the same donor. Recombinant virus strains are largely distinct. This is reflected in an unexpected diversity in recombination breakpoints and the relatively rare recombinations with identical recombination patterns of the same genotypes in different donors. Recent recombination events would explain the limited spread of each of the recombinants. Using a published mutation rate of 4.2×10(−5) mutations per site and year, the observed minimum genetic distances of 0–0.60% between parent strain and recombinant fragment would correspond to 0–71 years of evolution from a most recent common ancestor (MRCA). Thus several lines of evidence are suggestive of recent independent recombination events, a proportion of these even occurring within the same donors. In conclusion, our analyses revealed a high variability of mixed infections as a very probable breeding ground of multiple variable recombination events in Laos that so far have not led to new dominant strains.